Kepastian Hukum Penerapan Pasal 12B Ayat (1) Undang–Undang Nomor 20 Tahun 2001 Tentang Gratifikasi Dalam Kasus Tindak Pidana Korupsi Di Pengadilan Negeri Klas 1 A Kupang - Mo'a Belang, Ingrid Vianey Cendanawati; Manafe, Deddy R. CH.; Dima, Adrianus Djara (Law Faculty, Nusa Cendana University, 2025)
Corruption is categorized as part of special criminal law, which means it has specific characteristics that distinguish it from general criminal law. Unlike ordinary crimes, corruption involves abuse of power, tends to be systemic, and often includes complex financial transactions. It is widely recognized as an extraordinary crime and is frequently referred to as a white-collar crime because it typically involves individuals in positions of authority or influence. Due to its hidden and sophisticated nature, corruption poses a serious threat to the functioning of government institutions, public trust, and legal order. For these reasons, extraordinary legal instruments are essential in addressing and eradicating corruption effectively. This study focuses on two primary legal issues: (1) How is the reverse burden of proof applied in gratification cases at the Class 1A Kupang District Court? and (2) How is legal certainty upheld in the application of Article 12B paragraph (2) in the trial of corruption cases? The research uses a normative juridical approach, employing both conceptual and statutory methods, with deductive and/or inductive reasoning to obtain objective legal understanding. The reverse burden of proof under the Corruption Crime Law is applied mainly to examine unexplained increases in a defendant’s assets. The prosecutor must first show irregularities in the defendant’s assets, but the defendant must prove their legality. The unclear formulation risks undermining the presumption of innocence, so the reverse burden of proof should be a special exception balancing both parties’ rights.